Pore-Scale Modelling in Metal Foam Heat Exchanger - Chin, A.R. (Institute of Physics, 2022)
Increasing heat transfer performance of heat exchangers has been the primary focus in thermal engineering field. To ensure clean and affordable energy, in line with the UN SDG 7, an efficient thermal system is necessary. Various improvement strategies have been proposed, one that gaining considerable attention recently is application of metal foam. Among thermal system, metal foam offered the highest heat transfer rate. It offers larger heat transfer area and flow disruption that enhance overall heat transfer performance. All this while, most studies on metal foam are either experimental or simplified numerical model adopting homogeneous approach model which does not provide high fidelity information. Thus, this study is conducted to numerically investigate transport processes in metal foam heat exchangers by adopting three-dimensional pore-scale model which is expected to provide better accuracy and details on the transport processes in metal foam heat exchanger. The numerical study was initiated with the model development, followed by numerical implementation and finally numerical investigation. The numerical investigation reaffirms past studies that the presence of metal foam does bring enhancement to the heat transfer. However, it comes with the sacrifice on the significant increase in pressure drop. The adoption of pore-scale model revealed details of transport processes inside metal foam heat exchangers. Â© The Electrochemical Society